Inactivation of ricin by constituents present in a skin decontamination lotion. (25th September 2022) - van den Berg, R.M.; Joosen, M.J.A.; Savransky, V.; Cochrane, L.; Noort, D.
Abstract: Ricin is a proteinaceous toxin, listed on the schedules of both the chemical and biological weapons conventions. The ease of accessibility to the Ricinus communis plant and toxin extraction makes ricin a viable concern for use of intentional release and causal effects. The adverse effects following exposure to the toxin are caused by the bipartite molecular structure of ricin which allows binding to the mammalian cell surface, enter via endocytic uptake, and deliver the catalytically active polypeptide into the cell cytosol where it irreversibly inhibits protein synthesis, causing cell death. In the present study, the inactivation effectiveness of RSDL® (Reactive Skin Decontamination Lotion) and its individual inactivating constituents (Potassium 2, 3-butanedione monoximate (KBDO) and 2, 3-butanedione (DAM)) was evaluated for ricin using a number of read out systems including a cytotoxicity assay, quantitative sandwich ELISA test, and a mass spectrometry-based assay. The results demonstrate that RSDL is able to abolish ricin activity after an incubation time of 30 min as determined in the cytotoxicity assay, and after 2 min as determined in the ELISA assay. Mass spectrometric analysis provided evidence that RSDL is able to induce cleavage of the disulfide linkage between the A- and B- polypeptide chain of ricin which is crucial to the inactivation of the toxin, but this seems not the only mechanism of inactivation. Follow on studies would assist to elucidate the details of the toxin inactivation because it is possible that additional generic mechanisms are in place for denaturation with the RSDL lotion components. This may also provide a promise for testing and inactivation with RSDL of other protein toxins. Highlights: Reactive Skin Decontamination Lotion (RSDL) inactivates ricin within 2 min. Ricin inactivation by RSDL is caused by the K + salt of 2, 3-butanedione monoxime. Cleavage of the S–S bond in ricin's A- and B-chain might contribute to inactivation.